O Conselho Nacional de Direitos Humanos como instrumento de fortalecimento da democracia no Brasil (2009/2012) - Silva, Thalita Vitoria Castelo Branco Nunes (2015)
The policy councils are spaces for dialogue between state and society, whose aims are the democratization of public policy management and social control of civil society on governments. The bodies collegiate permanent and deliberative (or only advisory). In Brazil, there are already established councils at national, state and municipal levels, in several areas. It is understood that policy advice adds features of representative democracy, participatory and deliberative. Supported on this premise, the present study aims to analyze the importance of the National Human Rights Council in strengthening democracy in Brazil from 2009 to 2012. This council is one of the oldest in the country because it was created in 1964, fifteen days before the military coup. So if inquires: the National Council for Human Rights is an instrument of reinforcing democracy in Brazil from 2009 to 2012? In order to answer this question is adopted qualitative research, by the methods: hermeneutics and discourse analysis. The study was carried out the historical background of democracy as a political regime, in order to examine, especially the main features of representative democracy, participatory and deliberative. There was the institutionalization and the role of the National Human Rights Council in social participation in Brazil. It was emphasized the history and the work of this Council in the promotion and protection of human rights in Brazil. Through the analysis of the minutes, the bylaws, reports and council working legislation was possible to observe the argumentative process, the foundation of deliberative theory, through speech acts and political speeches made by the participants of the meetings of these spaces as well how to observe the participation and performance of the council. The survey results show that this advice was an instrument for strengthening of representative democracy, participatory and deliberative in the analyzed period; demonstrate, however, that much can be done to increase the effectiveness of democracy in that body, such as: increasing it greater autonomy from the government and making efforts for the creation and strengthening of the Human Rights Councils in the states and municipalities.